Rifampicin synergizes the toxicity of insecticides against the green peach aphid, Myzus persicae - Zengxin Li; Wenhong Li; Qing Mu; Yicheng Zhu; Weiwei Qin; Xiaobin Shi; Yueping He (Ecotoxicology and Environmental Safety, 2024)
Myzus persicae is an important pest that has developed resistance to nearly all currently used insecticidal products. The employment of insecticide synergists is one of the effective strategies that need to be developed for the management of this resistance. Our study showed that treatment with a combination of the antibiotic, rifampicin, with imidacloprid, cyantraniliprole, or clothianidin significantly increased their toxicities against M. persicae, by 2.72, 3.59, and 2.41 folds, respectively. Rifampicin treatment led to a noteworthy reduction in the activities of multifunctional oxidases (by 32.64%) and esterases (by 23.80%), along with a decrease in the expression of the CYP6CY3 gene (by 58.57%) in M. persicae. It also negatively impacted the fitness of the aphids, including weight, life span, number of offspring, and elongation of developmental duration. In addition, bioassays showed that the combination of rifampicin and a detoxification enzyme inhibitor, piperonyl butoxide, or dsRNA of CYP6CY3 further significantly improved the toxicity of imidacloprid against M. persicae, by 6.19- and 7.55-fold, respectively. The present study suggests that development of active ingredients such as rifampicin as candidate synergists, show promise to overcome metabolic resistance to insecticides in aphids.